The motive of the horse’s conversation with its owner-the hero in the epic “Jangar”: on the example of chapter «Bogdo noyan Jangar’s victory over the Shar Gerel Khan» - N. Oyunbilig (Nomadic Civilization: Historical Research)
The epic «Jangar» is an important type of folklore that was invented in the 15th century among the nearby peoples and spread among the entire Mongols. Dao’s beautiful country is a place that is full of happiness for the four seasons. Jangar’s origin, his glory, his subjects, his heroes, and their horses are clearly mentioned. Each hero is capable of charm and character, and it is important for future generations to understand «Jangar». This epic is essential for the transmission of culture and tradition. «Bogd noyon Jangar Shar Gerel khaanyg dailsan buleg» occupies a special place.